Sustainable Event Management: Penggunaan Teknologi Digital untuk Meningkatkan Keberlanjutan dalam Pengelolaan Acara - Devin Cumbuan Putri (Departement of Mathematics Education, 2024)
This study aims to explore sustainable event management through the use of digital technology, with a focus on how technology can enhance sustainability in the event industry. The methods used in this study include literature analysis and case studies of various events that have implemented sustainable practices. The sample involved includes event organizers, attendees, and other stakeholders in the MICE (Meetings, Incentives, Conferences, and Exhibitions) sector. The findings show that digital technologies, such as cloud-based management systems and data analytics, can significantly reduce environmental impacts, improve operational efficiency, and strengthen community engagement. However, challenges such as cybersecurity and the environmental impact of the technology itself also need to be addressed. Recommendations for future studies include further research on the long-term impact of digital technology in event management and the development of better planning guidelines. This study is expected to contribute to a better understanding of how technology can be used to achieve sustainability in event management.